ASPECT OF LANGUAGE FOREIGN EDUCATION IN PELANGI MELBOURNE BY ZUHAIRI MISRAWI (Structural Semiotic Study) - Rahmat Basuki (STKIP Persada Khatulistiwa Sintang, 2019)
Abstract : The reserach aims is identify and understand thoroughly foreign language education contained in Pelangi Melbourne Novel by Zahairi Misrawi. The research is qualitative Approach with analysis methode uses a structural study semiotic. The sourche of data is a Pelangi Melbourne Novel. The Data collected by reading over to understand and obtain data of foreign language education foreigners the factor personal and socio-cultural factors with semiotic structural study Methode.So, The data are grupp suitable foreigh learning theory. After that, Tha analyzing and doing interpretation is based on the theory foreign language learning. The researchers finded personal and social factors culture in Semiotic structural Study data are : form of icons 42 (36%) index of 58 (52%) and the symbol of 10 (13%). Third The semiotic is provide interpretation about foreign language education contained in the novel.Based on Pelangi Melbourne Novel, The Story gives an explanation that language education is not only requires learning English, but need the living environment and learning support. Personal, All students must have believe that self-nature both within the class and outside the classroom so that he is ready to communicate, eliminating anxiety and so forth. In addition, educational institutions must also be provide student residence so it is easy and convenient for students practice the English language without Indonesian rule out as national language.Keywords: Foreign Language, Education, Novel, factor personal, social and cultural factors, structural semiotic